Cardioprotective Effects of n-3 Polyunsaturated Fatty Acids: Orchestration of mRNA Expression, Protein Phosphorylation, and Lipid Metabolism in Pressure Overload Hearts - Li, Xiang; Tan, Weijiang; Zheng, Shuang; Zhang, Junjie; Zhu, Caiyi; Cai, Chun; Chen, Honghua; Yang, Chenqi; Kang, Le; Pan, Zhanhong; Pyle, W. Glen; Backx, Peter H.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Pressure overload can result in dilated cardiomyopathy. The beneficial effects of n-3 polyunsaturated fatty acids (n-3 PUFAs) on heart disorders have been widely recognized. However, the molecular mechanisms underlying their protective effects against cardiomyopathy remain unclear. Methods: Pressure overload in mice induced by 8 weeks of transverse aortic constriction was used to induce dilated cardiomyopathy. A transgenic fat-1 mouse model carrying the n-3 fatty acid desaturase gene fat-1 gene from Caenorhabditis elegans was used to evaluate the mechanism of n-3 PUFAs in this disease. Echocardiography, transmission electron microscopy, and histopathological analyses were used to evaluate the structural integrity and function in pressure overloaded fat-1 hearts. mRNA sequencing, label-free phosphoprotein quantification, lipidomics, Western blotting, RT-qPCR, and ATP detection were performed to examine the effects of n-3 PUFAs in the heart. Results: Compared with wild-type hearts, left ventricular ejection fraction was significantly improved (C57BL/6J [32%] vs. fat-1 [53%]), while the internal diameters of the left ventricle at systole and diastole were reduced in the fat-1 pressure overload hearts. mRNA expression, protein phosphorylation and lipid metabolism were remodeled by pressure overload in wild-type and fat-1 hearts. Specifically, elevation of endogenous n-3 PUFAs maintained the phosphorylation states of proteins in the subcellular compartments of sarcomeres, cytoplasm, membranes, sarcoplasmic reticulum, and mitochondria. Moreover, transcriptomic analysis predicted that endogenous n-3 PUFAs restored mitochondrial respiratory chain function that was lost in the dilated hearts, and this was supported by reductions in detrimental oxylipins and protection of mitochondrial structure, oxidative phosphorylation, and ATP production. Conclusions: Endogenous n-3 PUFAs prevents dilated cardiomyopathy via orchestrating gene expression, protein phosphorylation, and lipid metabolism. This is the first study provides mechanistic insights into the cardioprotective effects of n-3 PUFAs in dilated cardiomyopathy through integrated multi-omics data analysis.